2011
DOI: 10.1111/j.1526-4610.2011.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Burning Mouth Syndrome: A Therapeutic Approach Involving Mechanical Salivary Stimulation

Abstract: Salivary mechanical stimulation therapy is effective in reducing clinical symptoms of BMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
17
0
5
Order By: Relevance
“…Similarly, the levels of IgE did not significantly vary between resting and mechanically stimulated saliva, further highlighting the potential use of either method in a clinical setting when determining levels for monitoring immune response [32]. The effectiveness of mechanical stimulation as opposed to other methods of collecting saliva and detecting clinically-relevant proteins has been confirmed in previous studies [33-35]. Mechanically stimulated saliva is known to be predominantly derived from the parotid gland and consists mainly of water [27].…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, the levels of IgE did not significantly vary between resting and mechanically stimulated saliva, further highlighting the potential use of either method in a clinical setting when determining levels for monitoring immune response [32]. The effectiveness of mechanical stimulation as opposed to other methods of collecting saliva and detecting clinically-relevant proteins has been confirmed in previous studies [33-35]. Mechanically stimulated saliva is known to be predominantly derived from the parotid gland and consists mainly of water [27].…”
Section: Discussionmentioning
confidence: 79%
“…Borelli et al reported that nerve growth factor (NGF) peptide and tryptase activity were significantly and persistently higher in saliva of BMS subjects (Borelli et al, 2010). In a recent study, de Souza et al observed a significant reduction in the burning sensation and number of burning sites, as well as an improvement in taste disturbances and xerostomia, after mechanical salivary stimulation (de Souza et al, 2012). In their study, salivary stimulation therapy resulted in a significant decrease in salivary levels of total protein and an increase in tumor necrosis factor (TNF)-a.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also reported a decrease in serum TNF-α levels in this group [29], but yet others showed no significant differences between patients and controls regarding levels of salivary TNF-α [30,31]. Interestingly, BMS patients subjected to salivary stimulation therapy demonstrated a significant reduction of symptoms in parallel with a decrease in the salivary levels of total protein and an increase in TNF-α [32]. Elevated salivary concentrations of IL-6 in BMS patients have also been reported by some authors [8], but not by others [30,31].…”
Section: Discussionmentioning
confidence: 99%